Responder condicional e responder por exclusão em cães domésticos - Fenner, Marina Castana (Universidade Federal de São Carlos, 2015)
Exclusion is a behavioral process that seems to be found in human and non-human, in which, in the presence of an undefined sample stimulus, the participant excludes a defined comparison stimulus and selects a comparison stimulus that is also undefined. This study aimed to verify if exclusion could be replicated using the same procedure of the classic study of Dixon (1977) and dogs as experimental subjects. The procedure employed an automated apparatus that presented stimuli, recorded the operant responses on a touch screen and released food pallets, and a semi-automatic equipment, which performed all of the above functions, but reinforcement was released manually by the experimenter. The research was divided into three studies. Study 1 aimed to teach prerequisites to perform the experimental task; Study 2 had the intention to teach two audio-visual relations; and the Study 3 aimed to teach a second audio-visual relation and to verify the evidence of exclusion. Studies 1 and 2 made possible the completion of the Study 3. Study 3 was planned in four phases: C1Z1 Teaching - the Z1 visual stimulus was presented as S+ in response to a verbal command (C1), while two visual stimuli (Z2 and Z3) were presented as S-; Exclusion in the presence of new verbal commands used as samples (C2 and C3), the two visual stimuli, which before had Sfunction, took the S+ function; C2Z2 Teaching - the relation probed in the previous phase was directly taught (C2, Z2 + / Z1- and C2, Z2 + / Z3-); Exclusion - probes C3Z3 relationship, not directly taught. The results were analyzed in order to verify if the carried out procedures promoted: (1) conditional relations or a discrimination of the occasion to respond; and (2) exclusion. The results do not allow us to say with certainty whether the established control was only discriminatory or whether there was conditional control, which impedes a conclusion about the potential for exclusion responding in dogs. The discussion suggests that the teaching of conditional relations at the baseline requires switching between samples and their discriminative stimuli, without which the sample cannot acquire the conditional stimulus function, making the procedure a simple discrimination procedure.
Keywords: Psicologia do comportamento e cognição; Responder condicional; Responder por exclusão; Cão; Cães domésticos; Conditional relation; Exclusion; Domestic dogs; CIENCIAS HUMANAS::PSICOLOGIA